Mastitis Pathogens Mannheimia haemolytica, Staphylococcus aureus, and Streptococcus uberis Selectively Alter TLR Gene Transcription in Sheep Mammary Epithelial Cells - Riccardo Tassi; Helen Todd; Keith T. Ballingall (Microbiology Research, 2024)
Despite the impact of mastitis on sheep production worldwide, the pathogenesis and host response to bacterial infection of the ovine mammary gland are poorly characterized. Studies in cattle highlight the significance of the mammary epithelium in pathogen recognition and the subsequent host response. The objective of this study was to assess bacterial adherence, invasion, and Toll like receptor (TLR) gene expression in primary sheep mammary epithelial cells (pMEC) following co-culture with the three principal mastitis pathogens of sheep, Mannheimia haemolytica, Staphylococcus aureus, and Streptococcus uberis. S. aureus was 140-fold more adherent than S. uberis and 850-fold more adherent than M. haemolytica. However, only S. aureus was internalized after 3 h of co-culture. TLR1, 2, 3, 4, 6, and 9 were shown to be constitutively transcribed by pMEC. M. haemolytica induced upregulation of transcription of TLR1, 2, 3, and 4. By contrast, S. uberis and S. aureus induced concentration-dependent transcription of TLR2 and TLR4 with a higher level of transcription in cells stimulated with the bacteria at a multiplicity of infection (MOI) of 200 compared to cells stimulated with a MOI of 20. These experiments define the range of TLR genes constitutively transcribed in sheep pMEC and show that bacterial infection has the capacity to regulate transcription in a species-specific and concentration-dependent manner.